The Effectiveness of Sukuk Program Utilization In Increasing Community Income (Case Study of BSI Pamekasan Branch Office) - Holilur Rahman; Wawa Putri (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
State Sharia securities or sukuk have an important role in increasing people's income. Because in every issuance of this sukuk the state offers potential investors coupons or profit sharing, which is relatively high at 5-6% of deposits, but with high coupons so far the sukuk program has not been optimally utilized by the public. The purpose of this study was to determine the implementation of sales of sukuk and the effectiveness of the utilization of sukuk program in increasing people's income at Bank Syariah Indonesia Pamekasan Branch Office. The researchers used a qualitative approach. The method used is the method of interview, observation and documentation. The results of this study are the implementation of sales of sukuk in Bank Syariah Indonesia conducted online. The effectiveness of sukuk in increasing people's income is at a percentage level of 86%, this ranking explains if the sukuk program is currently included in the category of quite effective. This sukuk Program will be very effective if the purchase is above average.